Flat cat - Lazar, Tara (New York : Flamingo Books, 2023)
Flat Cat likes being flat--roaming anywhere and happy to be unseen--until one day when he becomes fluffy, he learns to enjoy the attention it brings, and grows to love being seen.
Ages 3-7
Grades K-1
Keywords: Cats -- Fiction; Self-acceptance -- Fiction; Humorous fiction; Picture books